Arkitektur og utstillinger som berører. En studie av nyere basisutstillinger i norske kunst- og kunstindustrimuseer - Sauge, Birgitte (Nordlit, 2015)
The intention with this article is to describe current exhibition practices at some Norwegian fine art- and design museums and to relate these practices to the visitors and their experiences, by comparing data concerning the plans and interior designs of gallery rooms and the organization of the displays. This investigation is based on data from a survey of 19 permanent exhibitions in 12 fine arts and design museums, conducted in 2011–12; the Norwegian museum architecture and museum displays with its more than 100 year old traditions; and Charlotte Klonk’s book Spaces of Experience: Art Gallery Spaces from 1800–2000. The survey shows that the purpose built museums to a large extent have kept their original layout and the organization of rooms. The non-purpose built museums tend to imitate the museums from the 1800s, within the limits of their given architecture. Different types of specially designed rooms are found in all buildings, regardless of age and purposes. Regarding the organization of displays, the most frequent principle is a combination of historically chronological types and themes. Almost as frequent are strictly historical chronological displays and thematic displays without any historical narrative. Hence, the comparisons reveal that there are no fixed patterns regarding the historical types and the conventions concerning the relationship between the museum architecture and organization of the displays, which lead to the conclusion that today there is no general curatorial strategy in Norwegian fine art- and design museums with regard to the visitors’ experiences.